2011
DOI: 10.1042/an20110018
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Inflammatory Responses in Transgenic Mouse Models of Alzheimer's Disease and the Effect of Immunotherapy on These Responses

Abstract: While the presence of an inflammatory response in AD (Alzheimer's disease) is well known, the data on inflammation are conflicting, suggesting that inflammation either attenuates pathology, exacerbates it or has no effect. Our goal was to more fully characterize the inflammatory response in APP (amyloid precursor protein) transgenic mice with and without disease progression. In addition, we have examined how anti-Aβ (amyloid β-peptide) immunotherapy alters this inflammatory response. We have used quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 51 publications
(72 reference statements)
5
47
2
Order By: Relevance
“…HHcy results in an M1-type neuroinflammation in WT mice [5]. We have also previously shown that amyloid-depositing Tg2576 mice show an M2a phenotype when amyloid has accumulated [18]. In the present study, we show that HHcy resulted in increased expression of the M1 markers interleukin 1β (IL-1β), tumor necrosis factor α, IL-12 and IL-6 in the APP/PS1 mice (Figure 6).…”
Section: Resultssupporting
confidence: 71%
“…HHcy results in an M1-type neuroinflammation in WT mice [5]. We have also previously shown that amyloid-depositing Tg2576 mice show an M2a phenotype when amyloid has accumulated [18]. In the present study, we show that HHcy resulted in increased expression of the M1 markers interleukin 1β (IL-1β), tumor necrosis factor α, IL-12 and IL-6 in the APP/PS1 mice (Figure 6).…”
Section: Resultssupporting
confidence: 71%
“…However Stahl et al (2006) reported that intracerebral infection of Tg2576 mice with the neurotropic Borna disease virus resulted in a decrease in Abcontaining plaques in hippocampus (Stahl et al, 2006). Increases in microglial activation and in expression of inflammatory cytokines were observed, prompting the authors to suggest that an inflammatory environment might enhance clearance of Ab, which has been supported by some groups (Wilcock et al, 2011) but not by others (Koenigsknecht-Talboo and Landreth, 2005;Yamamoto et al, 2007). Indeed it has been shown that an inflammatory environment, such as predominates in AD, inhibits efficient phagocytosis (Koenigsknecht-Talboo and Landreth, 2005), whereas the interaction of microglia with T cells has also been shown to switch microglia from a phagocytic to an APC phenotype (Townsend et al, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…These changes include the expression of various cell surface molecules (e.g., receptors and adhesion molecules) [38,41,57] and the secretion of cytokines and free radicals that influence microglia activation in both the autocrine and paracrine manner [93]. In the M1 state microglial cells are phagocytic/cytotoxic in nature, release various proinflammatory factors (e.g., cytokines and free radicals) enhance neuronal loss [35], and drive or exacerbate neurological complications [2,24,62,90,91]. In contrast, M2 state microglia express anti-inflammatory factors that suppress inflammation and promote immune-regulatory and repair/remodeling processes [27,36,37,55,57,84].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the process of inflammation is demonstrated in two states of microglia/macrophage polarization (M1 and M2 responses) [43,55,57,91]. The expression of various cytokines, receptors, receptor ligands, enzymes, and matrix proteins [57,78,82,89] plays a pivotal role in the secondary injury as well as recovery/regenerative processes.…”
Section: Introductionmentioning
confidence: 99%